Trace Solvent Additives Enhance Charge Generation in Layer‐by‐Layer Coated Organic Solar Cells. Issue 4 (26th February 2022) - Karuthedath, Safakath; Firdaus, Yuliar; Scaccabarozzi, Alberto D.; Nugraha, Mohamad Insan; Alam, Shahidul; Anthopoulos, Thomas D.; Laquai, Frédéric
Abstract : In bulk heterojunction (BHJ) organic solar cells (OSC), the photoactive layer morphology controls charge carrier generation, transport, and extraction. Obtaining the "optimum" morphology is often achieved by empiric optimization of processing conditions and post‐processing treatment. Better control over the morphology can be achieved by sequential photoactive layer‐by‐layer (LbL) deposition techniques, creating a pseudo‐bilayer OSC. Solvent additives can be used to modify the vertical component distribution, thereby enhancing OSC efficiency. However, the impact of solvent additives on device photophysics is often unclear. Here, the photophysics of LbL‐coated PM6/Y6 organic solar cells are reported. Enhanced power conversion efficiencies (PCEs) are observed when using 1‐chloronaphthalene (CN) as a solvent additive. Transient absorption (TA) spectroscopy indicates that the addition of 0.5% CN facilitates both exciton dissociation and charge separation, while excessive (>1%) use of CN causes fast geminate and non‐geminate charge recombination and consequently deteriorates device performance. The results outline routes to fine‐tune the morphology of LbL‐coated photoactive layers of OSCs and provide insight into the reasons for increased PCEs. Abstract : Increased power conversion efficiency (PCE) is observed when adding trace amounts of 1‐chloronaphthalene (CN) to Y6 in sequentially coated PM6/Y6 bilayer organic solar cells (OSCs). Transient absorption spectroscopy shows that the addition of 0.5–1% CN facilitates exciton dissociation and charge separation, while higher CN loadings increase charge recombination due to changes in the layer morphology.